Spatial coding in sonar imaging - Wang, Jingxi; Guo, Xin; Ge, Feng-Xiang; Arce, Gonzalo R (Electronics letters, 2017)
A practical deployment is presented for sonar imaging with fewer transmitters and receivers. Spatial coding via transmit beamforming is used for target detection and localisation. Transmit beamforming reduces the ambiguity in a model and improves imaging performance. To reconstruct the resultant underdetermined system of equations, a sparse signal reconstruction framework is used, and the inverse problem is solved by using an iterative optimisation algorithm. Deployment is optimised for better target detection and localisation performance. Successful sonar imaging reconstruction is guaranteed by the restricted isometry property with high probability. A numerical simulation shows that the proposed method can detect and localise targets efficiently, with better imaging results than those attained by conventional methods or the compressive sensing method without spatial coding.